2020
DOI: 10.1182/bloodadvances.2019001410
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory drugs suppress Th1-inducing ability of dendritic cells but enhance Th2-mediated allergic responses

Abstract: Immunomodulatory drugs (IMiDs), lenalidomide and pomalidomide, are widely used treatments for multiple myeloma; however, they occasionally lead to episodes of itchy skin and rashes. Here, we analyzed the effects of IMiDs on human myeloid dendritic cells (mDCs) as major regulators of Th1 or Th2 responses and the role they play in allergy. We found that lenalidomide and pomalidomide used at clinical concentrations did not affect the survival or CD86 and OX40-ligand expression of blood mDCs in response to lipopol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 83 publications
(90 reference statements)
0
12
0
Order By: Relevance
“…However, and interestingly, an increase in Th2 response has been observed after lenalidomide and pomalidomide treatment. Specifically, patients who developed an IMiDs-related skin rash obtained the best results in the anti-cancer response, raising the attention again on the importance of a Th2 response against MM [56].…”
Section: T Helper Responsementioning
confidence: 99%
“…However, and interestingly, an increase in Th2 response has been observed after lenalidomide and pomalidomide treatment. Specifically, patients who developed an IMiDs-related skin rash obtained the best results in the anti-cancer response, raising the attention again on the importance of a Th2 response against MM [56].…”
Section: T Helper Responsementioning
confidence: 99%
“…8,9 There are also some reports showing cases of eosinophilia with LEN treatment, 15,18,19 which stimulates Th2 memory cells by activation of T cells and dendritic cells (DC) with LEN. 10,[20][21][22] On the other hand, BOR has been shown to exert potent immunomodulatory effects, including the induction of apoptosis of DCs, the decrease in T-cell costimulatory molecules and inflammatory cytokine production, selective apoptosis of activated effector T cells, and inhibition of NF-κB. 13,14 Therefore, it was considered that the development of LEN-induced skin rash could be reduced by the prior administration of BOR.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism of LEN-induced skin rash is not clearly understood, it is thought that T cells are importantly involved in its appearance. [14][15][16] It has also been reported that the incidence of LEN-induced skin rash decreases with a history of chemotherapy (especially BOR), 17,18 which has a cell-mediated immunosuppressive effect. Demir et al described a desensitization protocol using corticosteroids, 12 which also has immunosuppressive effects.…”
Section: What Is Ne W and Con Clus I Onmentioning
confidence: 99%